Upgrading of the high-current accelerator “Tonus” - Ryabchikov, A.I.; Petrov, A.V.; Karpov, V.B.; Polkovnikova, N.M.; Tolmacheva, V.G.; Usov, Yu.P. (Вопросы атомной науки и техники, 2001)
In the paper presented, the new technical development of the high-current electron accelerator “Tonus-NT” (Tomsk nanosecond accelerator – new technologies) is described. It has been developed taking into account the experience of 30-years exploitation of the previous analogue – the accelerator “Tonus”. The scheme of the accelerator includes the high-voltage transformer with resonant contours (Tesla transformer) charging the double forming line filled with the transformer oil and the high-voltage diode. The gas-filled trigatron spark gap with up to 10 atm operating pressure is used for the double forming line switching. The main accelerator parameters are as follows: accelerating voltage range 0.4-1.7 MeV, line impedance 36.6 Ω, pulse duration 60 ns, pulse repetition rate up to 10 pps.